Metabolism of Carotenoids and β-Ionone Are Mediated by Carotenogenic Genes and PpCCD4 Under Ultraviolet B Irradiation and During Fruit Ripening - Liu, Hongru; Cao, Xiangmei; Azam, Muhammad; Wang, Chunfang; Liu, Chenxia; Qiao, Yongjin; Zhang, Bo (Frontiers in Plant Science, 2022)
Carotenoids are essential pigments widely distributed in tissues and organs of higher plants, contributing to color, photosynthesis, photoprotection, nutrition, and flavor in plants. White- or yellow-fleshed colors in peach were determined by expression of carotenoids cleavage dioxygenase (PpCCD) genes, catalyzing the degradation of carotenoids. The cracked volatile apocarotenoids are the main contributors to peach aroma and flavor with low sensory threshold concentration. However, the detailed regulatory roles of carotenoids metabolism genes remained unclear under UV-B irradiation. In our study, metabolic balance between carotenoids and apocarotenoids was regulated by the expression of phytoene synthase (PSY), β-cyclase (LCY-B), ε-cyclase (LCY-E), and PpCCD4 under UV-B irradiation. The transcript levels of PpPSY, PpLCY-B, PpLCY-E, and PpCHY-B were elevated 2- to 10-fold compared with control, corresponding to a nearly 30% increase of carotenoids content after 6 h UV-B irradiation. Interestingly, the total carotenoids content decreased by nearly 60% after 48 h of storage, while UV-B delayed the decline of lutein and β-carotene. The transcript level of PpLCY-E increased 17.83-fold compared to control, partially slowing the decline rate of lutein under UV-B irradiation. In addition, the transcript level of PpCCD4 decreased to 30% of control after 48 h UV-B irradiation, in accordance with the dramatic reduction of apocarotenoid volatiles and the delayed decrease of β-carotene. Besides, β-ionone content was elevated by ethylene treatment, and accumulation dramatically accelerated at full ripeness. Taken together, UV-B radiation mediated the metabolic balance of carotenoid biosynthesis and catabolism by controlling the transcript levels of PpPSY, PpLCY-B, PpLCY-E, and PpCCD4 in peach, and the transcript level of PpCCD4 showed a positive relationship with the accumulation of β-ionone during the ripening process. However, the detailed catalytic activity of PpCCD4 with various carotenoid substrates needs to be studied further, and the key transcript factors involved in the regulation of metabolism between carotenoids and apocarotenoids need to be clarified.